Oral manifestations of illicit drug use - Das, Anuttam; Jalaluddin, Mohammad; Sahu, Natasha; Kar, Souvagya R.; Brahma, Priyanka; Panigrahi, Priyanca (International Journal of Research in Medical Sciences, 2022)
Oral health problems, among the most prevalent comorbidities related to addiction, require more attention by both clinicians and policy-makers. Our aims were to review oral complications associated with drugs, oral health care in addiction rehabilitation, health services available, and barriers against oral health promotion among addicts. Drug abuse is associated with serious oral health problems including generalized dental caries, periodontal diseases, mucosal dysplasia, xerostomia, bruxism, tooth wear, and tooth loss. Oral health care has positive effects in recovery from drug abuse: patients’ need for pain control, destigmatization, and human immune-deficiency virus (HIV) transmission. Health care systems worldwide deliver services for addicts, but most lack oral health care programs. Barriers against oral health promotion among addicts include difficulty in accessing addicts as a target population, lack of appropriate settings and of valid assessment protocols for conducting oral health studies, and poor collaboration between dental and general health care sectors serving addicts. These interfere with an accurate picture of the situation. Moreover, lack of appropriate policies to improve access to dental services, lack of comprehensive knowledge of and interest among dental professionals in treating addicts, and low demand for non-emergency dental care affect provision of effective interventions. Management of drug addiction as a multi-organ disease requires a multidisciplinary approach. Health care programs usually lack oral health care elements. Published evidence on oral complications related to addiction emphasizes that regardless of these barriers, oral health care at various levels including education, prevention, and treatment should be integrated into general care services for addicts.